Structured Flexibility in Ummi Method Quality Assurance: Balancing Control and Contextual Adaptation Across Islamic Educational Institutions - Imam Azhar; Zainul Fuad (MADINAH, 2026)
This study examines the implementation of quality assurance mechanisms in Qur'anic learning through the UMMI Method across diverse Islamic educational institutions; investigating patterns of fidelity, adaptation, and the tensions between standardization and contextual flexibility. A mixed-method design was employed with a sample of 50 institutions. Quantitative data comprised supervision assessments across ten quality assurance domains, while qualitative data from 347 pages of supervisory notes underwent systematic six-stage coding. Correlation analysis demonstrated strong relationships between quality control systems and student reading quality (r = 0.669, p < 0.001), and between student grouping systems and coordinator qualifications (r = 0.653, p < 0.001). However, institutional commitment showed non-significant correlations with most implementation variables. Qualitative findings revealed four quality assurance mechanisms teacher certification, standardized learning materials, seven-step methodology, and centralized quality control alongside three implementation tensions: resource constraints, cultural integration challenges, and standardization-contextualization tensions. This study introduces structured flexibility a quality assurance model that balances methodological fidelity with contextual adaptation. This independent, large-scale mixed-methods study provides empirical evidence on how quality assurance operates in religious education, contributing to the emerging literature on the quality of Islamic education and offering a framework applicable to diverse religious educational contexts